Daidalos and the origins of Greek art - Morris, Sarah P., 1954- (Princeton University Press, 1995)
In a major revisionary approach to ancient Greek culture, this title invokes as a paradigm the myths surrounding Daidalos to describe the profound influence of the Near East on Greece's artistic and literary origins.